TOXOCARIASIS AND COCCIDIASIS IN DOMESTIC CAT - Gusti Agung Ayu Alecia Putri Anugrahaeni; I Putu Gede Yudhi Arjentinia; Sri Kayati Widyastuti (Buletin Veteriner Udayana, 2025)
Toxocariasis and coccidiasis are parasitic diseases frequently found in domestic cats and can cause gastrointestinal disorders such as diarrhea, anorexia, and decreased body condition. This report aims to describe the symptoms, diagnostic methods, and treatment of Toxocara sp. and Isospora sp. infections in a domestic cat. This case discusses Toxocara sp. and Isospora sp. infections in a domestic cat named Mail, who exhibited clinical symptoms of chronic diarrhea, weakness, and changes in stool condition. Examination was conducted through history taking, clinical examination, fecal floatation and sediment tests, and a Complete Blood Count (CBC) examination. The results showed the presence of Isospora sp. oocysts, both sporulated and non-sporulated, and Toxocara sp. eggs, accompanied by anemia and leukocytosis. Therapy using Pyrantel pamoate, Praziquantel, Metronidazole, and iron supplements was given during the treatment period. After 20 days, the cat's condition improved, indicated by more solid stools and increased activity. It was concluded that rapid diagnosis and appropriate therapy can accelerate recovery. Maintaining environmental sanitation, routine deworming, and improving husbandry management are recommended to prevent reinfection.